COOPERATIVE LEARNING STRATEGY IN CRITICAL READING ENGLISH TEXT THROUGH TEAM GAME TOURNAMENT (TGT) AND JENGA - Fuzi Fauziyah; Siti Gina Meilani; Salsabila Salsabila (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
The rapid development of information has the potential to spread negative content such as hoax news, hate speech, or issues of radicalism and intolerance. In this case, critical reading skills are needed. By reading critically, readers can become more objective, able to sort and not easily swayed. However, the learning implementation of critical reading is not easy, especially coupled with the students' low reading interest and ability, especially towards English reading texts. This narrative review aims to examine cooperative learning strategies in critical reading of English texts through Team Game Tournament (TGT) and Jenga. The method used is literature study by examining various sources from journal articles in various databases, proceedings, and official websites on critical reading, cooperative learning, TGT, and Jenga games. The selected data is then reduced, classified, analyzed, and concluded. The results of literature search show that in critical reading students not only understand the content of the text but also analyze and evaluate the text they read. In this case, cooperative learning facilitates students to critically exchange ideas about the insights, ideas, and points of view they get from the text. TGT, as a form of cooperative technique, has advantages of making students work together to try to improve critical reading scores quickly and accurately in groups. In practice, Jenga which is believed to have the superiority of cooperative, communicative, and effective aspects can be used by modifying and adding questions related to critical reading so that students try to understand and analyze the text accurately. Seeing the advantages of TGT as a cooperative learning strategy and the benefits of the Jenga in critical reading, the integration between the two can facilitate three important aspects, namely critical, fast and accurate so that it has the potential to develop students' critical reading skill in reading English text.Keywords: critical reading, cooperative learning, team game tournament (TGT), jenga